2018
DOI: 10.1177/2394481118774489
|View full text |Cite
|
Sign up to set email alerts
|

Health Equity in India: An Examination Through the Lens of Social Exclusion

Abstract: To ensure health care access among the vulnerable and the poor is the prerogative of the State since the financial burden of curative care is higher among lower income groups, most of whom are Dalits. In the last 70 years, India has achieved considerable improvement in the health of its people. Nonetheless, the gap across social groups remains wide. There is evident association of low health status with poor, female gender, rural place of residence, tribal ethnicity, scheduled castes (SC) and specific minority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 28 publications
(38 reference statements)
0
31
0
Order By: Relevance
“…rural versus urban [28]. Studies in India also showed that the underprivileged groups like the nancially weak, poorly literate, or living in rural areas, had limited access to healthcare services, thus leading to poorer outcomes for health [29] [30]. Similar ndings were observed in the case of Pakistan and for the provinces except for Balochistan where the inequities continue to prevail in the same ratio during throughout the last decade.…”
Section: Discussionmentioning
confidence: 59%
“…rural versus urban [28]. Studies in India also showed that the underprivileged groups like the nancially weak, poorly literate, or living in rural areas, had limited access to healthcare services, thus leading to poorer outcomes for health [29] [30]. Similar ndings were observed in the case of Pakistan and for the provinces except for Balochistan where the inequities continue to prevail in the same ratio during throughout the last decade.…”
Section: Discussionmentioning
confidence: 59%
“…Thus the poor are the victims of unregulated spread of private health services, as they require better care at affordable cost. There are increasing gaps in health care utilization by different income groups from both public and private sectors in the country; and the high income groups benefit from the better quality health care from the private hospitals as well as subsidized health care from the government hospitals (Acharya, 2018;Baru et al, 2010). Within private sector, the spectrum of quality of care is widely varied (Baru, 2013).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…The lack of awareness about disease management, inequitable distribution of health care facilities in rural areas coupled with high cost of SMBG test strips, financial constraints have led to comparatively decreased utilization of SMBG in rural areas. 14,15 The specialized health-care centres which are located in urban areas, generally provide more comprehensive medical care with greater focus on patient satisfaction with their medical care and patient-provider relationship. 1,14,15 This is also reflected in the present study wherein a significantly lesser percentage of diabetics from rural areas practised SMBG when compared to the diabetics who were residents of urban areas (Table 2).…”
Section: Discussionmentioning
confidence: 99%